Educating in Uncertainty: Research on Teaching and Learning as a Horizon for Universities in the 21st Century - García Hormazábal, Ricardo (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
The twenty-first-century university faces unprecedented complexity, uncertainty, and diversity, driven by social, technological, and cultural transformations that demand the preparation of professionals capable of addressing both global and local challenges. This article examines how the integration of research on teaching and learning can serve as a strategic axis for higher education institutions to respond to these challenges. Adopting a conceptual and analytical approach, this study synthesizes evidence from the Scholarship of Teaching and Learning (SoTL) and the Science of Learning to explore their complementary roles in shaping effective pedagogical practices. The findings indicate that research-informed teaching strengthens reflective competencies, promotes pedagogical innovation, and supports teachers’ professional development, while also informing curriculum design and fostering inclusive, adaptive, and collaborative learning environments. For students, this integration leads to deep and meaningful learning, fostering critical thinking, collaboration, and self-regulation skills. The significance of these results lies in the fact that aligning evidence-based teaching and learning strategies with institutional goals enables the university to operate as a dynamic ecosystem where research informs practice and learning, in turn enriching inquiry. This approach safeguards against misinformation and shallow learning, prepares graduates to navigate complex professional and social realities, and positions the university as a resilient and socially relevant model.